Hospital-acquired bloodstream infections in patients deceased with COVID-19 in Italy (2020–2021) - Monaco, Monica; Floridia, Marco; Giuliano, Marina; Palmieri, Luigi; Lo Noce, Cinzia; Pantosti, Annalisa; Palamara, Anna Teresa; Brusaferro, Silvio; Onder, Graziano; , The Italian National Institute of Health COVID-19 Mortality Group; Palmieri, Luigi; Agazio, Elvira; et al. (Frontiers in Medicine, 2022)
Introduction In hospitalized patients with COVID-19, bloodstream infections (BSI) are associated with high mortality and high antibiotic resistance rates. The aim of this study was to describe BSI etiology, antimicrobial resistance profile and risk factors in a sample of patients deceased with COVID-19 from the Italian National COVID-19 surveillance. Methods Hospital charts of patients who developed BSI during hospitalization were reviewed to describe the causative microorganisms and their antimicrobial susceptibility profiles. Risk factors were analyzed in univariate and multivariate analyses. Results The study included 73 patients (71.2% male, median age 70): 40 of them (54.8%) received antibiotics and 30 (41.1%) systemic steroids within 48 h after admission; 53 (72.6%) were admitted to intensive care unit. Early steroid use was associated with a significantly shorter interval between admission and BSI occurrence. Among 107 isolated microorganisms, the most frequent were Enterococcus spp., Candida spp., Acinetobacter baumannii, and Klebsiella pneumoniae. Median time from admission to BSI was shorter for Staphylococcus aureus compared to all other bacteria (8 vs. 24 days, p = 0.003), and longer for Enterococcus spp., compared to all other bacteria (26 vs. 18 days, p = 0.009). Susceptibility tests showed a high rate of resistance, with 37.6% of the bacterial isolates resistant to key antibiotics. Resistance was associated with geographical area [adjusted odds ratio (AOR) for Central/South Italy compared to North Italy: 6.775, p = 0.002], and with early use of systemic steroids (AOR 6.971, p = 0.018). Conclusions In patients deceased with COVID-19, a large proportion of BSI are caused by antibiotic-resistant bacteria. Early steroid use may facilitate this occurrence.